Power Doppler Sonography and Clinical Monitoring for Hyaluronic Acid Treatment of Rhizarthrosis: A Pilot Study - Ingegnoli, Francesca; Soldi, Amedeo; Meroni, Pier Luigi (Journal of Hand and Microsurgery, 2011)
Trapeziometacarpal (TMC) joint osteoarthritis (OA) is a common disabling condition in which the impact of visco-supplementation has to be ascertained. We aim to evaluate the efficacy of high molecular weight hyaluronic acid (HA) ultrasound (US)-guided intra-articular injection of TMC joints in OA. 32 TMC joints of 16 patients with symptomatic thumb base OA were treated with three injections of high molecular weight HA at 1-week intervals. Before injection, at week 0, 1, 2, and 24 all patients underwent clinical and US examination. A significant clinical improvement was obtained by the decrease in visual analog scale for pain after 2 weeks of treatment (p=0.0003) and this result is maintained at week 24 (p=0.009). The Dreiser’s index also decreased after week 2 and remain stable after 6 months. Power Doppler signal significantly decreased after 2 weeks of treatment (p=0.02), even if this result was not maintained at week 24. No significant decrease in the synovial hypertrophy score was observed during the study. Our preliminary study suggests that US-guided TMC injections by high molecular weight HA may be effective in decreasing local inflammation and pain.
Keywords: Rhizarthrosis; Hyaluronic acid; Ultrasonography